Penerapan Cisco Packet Tracer Sebagai Media Pembelajaran Jaringan Untuk Meningkatkan Hasil Belajar Siswa Pada Kelas X TKJ di SMK 2 Ibrahimy Sukorejo - Arico Ayani Suparto; Rahmat Shofan Razaqi (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2019)
To improve the quality of learning can be done by applying strategies or methods of effective learning in the classroom, empower students and utilize existing resources in the school environment. Student activity in teaching and learning activities is marked by the participation of students in carrying out the task given by the teacher. Low student learning activities will have an impact on student’s non-completeness. One of the factors that influence the lesson that is applied by the teacher is less arousing student’s learning. The purpose of this research is to know the increase of activity and student learning outcomes trought application of Learning Media Using Cisco Packet Tracer Application To Improve Student Learning Outcomes of Class X In Basic Network Subject In SMK 2 Ibrahimy Sukorejo Lesson year 2018/2019. This research was conducted from28 April – 1 Mei 2018 with the object of research that is students class X TKJ as many 24 student. To obtain data in research using the method of observation, test and documentation. Data analysis in this research use qualitative descriptive analysis. The results obtained in the study showed improvement in student learning outcomes. In the pre-cycle of of classical completeness 54%, after the action of research daily repetition in cycle I obtained 66% classical completeness. This indicates an increase in student learning outcomes, althought the Cisco Packet Tracer application learning in cycle I has not yet achieved the caliber of learning. The Cisco Packet Tracer application is continued in cycle II. The result of daily test analysis on cycle II was 87% classical completeness, it shows that the result achievement of learning completeness in classical. The conclusion in this rearch that the learning model used by the teacher is very influence to the activity and result of student learning, it is proven that in applying of learning Cisco Packet Tracer application can improve result of activity and result of student learning of X TKJ class on basic network subjek to scores of 85% classically